Pianomania [videorecording (DVD)] - Franck, Lilian, 1971-; Franck, Lilian, 1971-; Knüpfer, Stefan, 1967-; Aimard, Pierre-Laurent, 1957-; Lang, Lang, 1982-; Brendel, Alfred; Fellner, Till, 1972-; Drake, Julius, 1959-; Joo, Hyung-ki (First Run Features, 2010)
As Steinway & Sons' chief technician and master tuner in Vienna, Stefan Knüpfer is dedicated to the unusual task of pairing world-class instruments with world-famous pianists. Juggling the demands of the pianist, the piano, and the piece to find the perfect match requires boundless enthusiasm, but also endless patience and nerves of steel. No detail is too small or too inconsequential for Knüpfer, not even the tiniest speck of dust on a piano string.